Predictors of Knowledge-Sharing Behaviors Among Community-Based Natural Resources Organizations in the Okavango Delta, Botswana - Thakadu, Olekae T.; Irani, Tracy A.; Telg, Ricky (Science communication, 2013)
The study investigated the relative contribution of selected predictors of knowledge-sharing behaviors among local community leaders involved in natural resources management programs within the Okavango Delta, Botswana. The theory of reasoned action and the responsible environmental behavior framework guided the study. Thirteen community-based natural resources management projects’ boards of trust, comprising a total of 120 subjects, participated in a quasi-experimental study. Results indicate that a combination of knowledge, attitude, and locus of control significantly predicts knowledge-sharing intentions, with knowledge and attitudes as the most important predictors. Implications and recommendations for practice are discussed, and directions for future research are suggested.